Por uma poética da fragilidade. Para um museu dos Bonecos de Santo Aleixo - José Alberto Ferreira (Midas: Museus e Estudos Interdisciplinares)
The Bonecos de Santo Aleixo constitutes a cultural and artistic heritage that originated as a performative practice of large regional significance in Alentejo (Portugal). To ensure its preservation, the continuity of its practice, as well as its dissemination, the Bonecos de Santo Aleixo were the subject of a transfer of ownership by its last owner, master Talhinhas. Hence, over the past 30 years, they have remained deposited as a tradition in the hands of a theatre company, the Centro Cultural de Évora, which preserved and presented the Bonecos de Santo Aleixo all over the world. Currently, the issue of the preservation of this heritage through its musealisation as been raised, given the regional, national and international recognition it has acquired, while the fragility of its material elements imposes a certain urgency to the process. Scrutinizing the relationship of the performing arts with the museum, one finds an increasing orientation of the museum practices towards live events, but also a strong resistance. My claim here is for a museum concerning tangible and intangible heritage, a museum including not only the puppets and all the objects they come with, but also the embodied knowledge that performing them involves as heritage. Therefore, I advocate for a school-museum, where the preservation and learning go together, in order to keep the spectacular repertoire of Bonecos de Santo Aleixo alive.